The impact of school culture on the quality of education in Vietnamese teacher training colleges: a case study in the Red River Delta - Thi Quynh, Vu; Ngoc Son, Pham (International Journal of Evaluation and Research in Education (IJERE), 2025)
School culture is a system of beliefs, values, norms, habits, and traditions developed throughout the school’s evolution, recognized and followed by its members, and expressed in both material and spiritual forms. This unique identity shapes each educational institution. The school’s culture influences the behavior, attitudes, goals, and outcomes of its students. Based on the intrinsic nature and role of school culture, this study clarifies the correlation between culture and training quality in teacher training colleges in the Red River Delta, Vietnam. Through survey results, observations, and interviews, this research establishes a significant correlation between positive cultural elements and enhanced educational quality indicators, including student achievement, teacher satisfaction, and research productivity. Conversely, negative cultural aspects are found to adversely impact these indicators. The study emphasizes the vital role of school culture in shaping educational experiences and outcomes in Vietnamese teacher training colleges. Based on these findings, the research offers practical recommendations for fostering a positive school culture, thereby contributing to the improvement of teacher training quality in Vietnam.